HAK ASASI MANUSIA DAN KEADILAN BERMARTABAT: PERBANDINGAN TEORI DAN REALITAS DI INDONESIA - Alexander Kennedy (LPPM Universitas Ekasakti, 2024)
Protection of Human Rights (HAM) in Indonesia has been mandated and maintained by the laws and regulations of the Republic of Indonesia. However, the reality on the ground shows that there are a number of obstacles, including human rights violations by individuals, restrictions on freedom, and limitations in upholding human rights. Therefore, contributions from the theory of dignified justice are needed to overcome this problem. The research method applied in this research is a normative legal study using a statutory approach. Then the research results will be analyzed descriptively, analytically and prescriptively. The research results show that the theory of dignified justice places Pancasila as the highest source of law, linking it to justice and political ethics. Dignified justice emphasizes that the law must humanize humans and create a dignified society. By focusing on the essence of law, this theory creates a strong connection between values in the legal system. The reality of Human Rights (HAM) in Indonesia, as recognized by Law Number 39 of 1999, emphasizes that human rights are a gift from God that is inherent in human nature. Even though it is absolute and universal, there are serious challenges such as human rights violations, restrictions on freedom, and suboptimal enforcement. Issues involve violence, child abuse, bullying, and the injustice of the legal system.